In situ identification of water-permeable fractured zone in overlying composite strata - Huang, W.P.; Li, C.; Zhang, L.W.; Yuan, Q.; Zheng, Y.S.; Liu, Y. (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2018)
The height and boundary shape of a water-permeable fractured zone (WFZ) play an important role in mining safety under challenging conditions; for example, when the coal seam is subject to a confined aquifer or the roadway is designed in close range to the coal seam. For the accurate estimation of the WFZ height, the theoretical prediction method was introduced based on the overlying composite strata structure and an empirical equation. In situ detection of the WFZ height and shape was performed in the Zhaizhen coal mine, China. The field detection was executed by injecting water into boreholes. Based on the analysis results of the variation in water seepage along these boreholes, the fracture intensity and the permeability of the overlying strata were studied, and the height and boundary shape of the WFZ were also confirmed. The measured height was consistent with the theoretical estimation, verifying that the WFZ developed upwards through the strata group acting as a unit. The final boundary of the WFZ presented an irregular saddle shape, and the boundary angle was approximately 75°–78°. According to the height and shape of the WFZ induced by mining of the lower coal seam, the fracture intensity and scope of the surrounding rock and the mining feasibility of the upper coal seam was evaluated in the Zhaizhen mine. A suitable roadway layout of the upper coal seam was also designed.